O controle social, a intersetorialidade e as condições operacionais da proteção social básica no município de Montes Claros - MG - Perez, Adriana Medalha (2013)
The Unified Social Assistance brings new guidelines, rules, flows and procedures for the implementation of the Brazilian social assistance. This study aimed to evaluate the Basic Social Protection of the Unified Social Assistance offered through the so-called Reference Centres for Social Assistance-CRAS in Montes Claros / MG, highlighting three dimensions: social control, intersectoral and operating conditions . The direction of this evaluation is guided by typing in PSB National social assistance services. The methodological procedures that supported this study were the evaluation process, the qualitative research, which included the use of questionnaires and semi-structured interviews with two representatives of the management of His, 4 aldermen, and two representatives of civil society and two government, municipal councils of social welfare, children and adolescents, the elderly and people with disabilities and the coordinators of the 11 CRAS. The research pointed out that efforts will have little effect for the improvement of policy design and improvement of the management mechanisms of the system if they do not reach the tip of an honest and fair, because the CRAS is the indicator par excellence for calibration the efficiency of their management procedures and the effectiveness of the provisions of national policy it implements.